2003
DOI: 10.1074/jbc.m303527200
|View full text |Cite
|
Sign up to set email alerts
|

Ssq1, a Mitochondrial Hsp70 Involved in Iron-Sulfur (Fe/S) Center Biogenesis

Abstract: The results of in vivo and in organellar experiments indicate that the Hsp70 Ssq1 and the J-protein Jac1 function together to assist in the biogenesis of ironsulfur (Fe/S) centers in the mitochondrial matrix. Here we present biochemical evidence supporting this idea. Isu, the proposed scaffold on which Fe/S centers are assembled, is a substrate for both Jac1 and Ssq1. Jac1 and Isu1 cooperatively stimulate the ATPase activity of Ssq1. In addition, Jac1 facilitates the interaction of Ssq1 with Isu1 in the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
142
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(147 citation statements)
references
References 42 publications
5
142
0
Order By: Relevance
“…Both Ssq1 and Hsc66 and their respective co-chaperones Jac1 and Hsc20 interact independently with Isu/IscU. In addition, Isu/IscU and Jac1/Hsc20 cooperatively stimulate Ssq1/Hsc66 ATPase activity, a strong indication that Isu/IscU is a substrate for the chaperone systems (7,16).…”
mentioning
confidence: 87%
See 3 more Smart Citations
“…Both Ssq1 and Hsc66 and their respective co-chaperones Jac1 and Hsc20 interact independently with Isu/IscU. In addition, Isu/IscU and Jac1/Hsc20 cooperatively stimulate Ssq1/Hsc66 ATPase activity, a strong indication that Isu/IscU is a substrate for the chaperone systems (7,16).…”
mentioning
confidence: 87%
“…As expected of an Hsp70-J-protein-substrate interaction, Jac1 interacts with Isu independently of adenine nucleotide, although the interaction of Isu with Ssq1 is nucleotide-dependent (7). Typical of an Hsp70-substrate interaction, Isu binds stably to Ssq1 in the presence of ADP, whereas no direct interaction between Isu and Ssq1 has been detected in vitro in the presence of ATP.…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…Using purified proteins, it was shown that Ssc1 can mediate ATP-dependent disaggregation and proper refolding of stably misfolded reporter proteins, when supplemented with bacterial DnaJ and GrpE (De Los Rios et al 2006). Ssq1 is known to play a role in the biogenesis of iron sulfur clusters and the function of Ecm10 is still unclear (Baumann et al 2000;Dutkiewicz et al 2003).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%